1995
DOI: 10.1007/bf01384340
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic relationships of hantavirus strains analysed by monoclonal antibodies

Abstract: The antigenic relationships among 71 hantavirus strains, isolated from rodent species or humans in several geographic regions, were examined by immunofluorescence assay (IFA) using human patient sera and a panel of 22 monoclonal antibodies prepared against Hantaan, Seoul, and Puumala viruses. The study included virus strains, mainly from the former USSR, for which little or no serological data were available. Fifty-nine of the 71 isolates could be placed into five antigenic groups of hantaviruses, Hantaan (HTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…N protein-specific antibodies induced by natural infection in human and experimental infections and immunizations in rodents have been found to be highly cross-reactive between different hantaviruses (9,11,12,14,37). However, we observed that 2 and 1 out of 23 acute-phase sera from DOBV-infected patients reacted exclusively with the IgM and IgA ELISA, respectively, based on the DOBV rN protein but were not detected by use of the related HTNV rN protein.…”
Section: Discussioncontrasting
confidence: 58%
“…N protein-specific antibodies induced by natural infection in human and experimental infections and immunizations in rodents have been found to be highly cross-reactive between different hantaviruses (9,11,12,14,37). However, we observed that 2 and 1 out of 23 acute-phase sera from DOBV-infected patients reacted exclusively with the IgM and IgA ELISA, respectively, based on the DOBV rN protein but were not detected by use of the related HTNV rN protein.…”
Section: Discussioncontrasting
confidence: 58%
“…The reactivities of the anti-mouse conjugates to immunoglobulins from different rodent species were determined by titration. A pool of bank vole monoclonal antibodies (MAb; 1C12, 2E12 and 4C3), directed to epitopes conserved in the different hantaviruses, was used as a positive, internal control Dzagurova et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…This Fab identified a novel epitope designated G2c which is shared by PUU and KBR, but not PH. KBR is a recently discovered hantavirus isolated from Microtus fortis in far-eastern Russia and has been identified as distinct but closely related to PH and PUU on the basis of serological data and genetic analysis (Dzagurova et al, 1995 ;Ho$ rling et al, 1996). Since PUU is pathogenic to humans, in contrast to PH, further characterization of such epitopes may give clues to hantavirus pathogenicity.…”
Section: Ggcmentioning
confidence: 99%